Association Between White Blood Cells at Baseline and Treatment Failure of MTX for Ectopic Pregnancy - Chen, Si; Chen, Xiao-Feng; Qiu, Pin; Huang, Yan-Xi; Deng, Gao-Pi; Gao, Jie (Frontiers in Medicine, 2021)
Purpose: The aim of this study was to evaluate white blood cell (WBC) count as a risk factor related to methotrexate (MTX) treatment failure in patients with ectopic pregnancy (EP). Methods: A total of 236 women diagnosed with EP and treated with a single-dose of MTX were included. The exposure variable was WBC count at baseline and the outcome was MTX treatment outcome. Both a multivariate binary logistics regression model and subgroup analysis were performed to evaluate the association between WBC and MTX non-response. Results: WBC count was associated with the risk of treatment failure, and the odds ratio (OR) in different multivariate models were stable (minimally adjusted model: OR 1.2, 95% confidence interval (CI): 1.0–1.3, P = 0.008; fully adjusted model: OR 1.2, 95% CI: 1.0–1.4, P = 0.026). When WBCs in group T3 (>8.9 × 109/L), the association between WBC count and treatment failure was significant (minimally adjusted model: OR: 2.0, 95% CI: 1.0–3.8, P = 0.050; fully adjusted model: OR: 2.2, 95% CI: 1.1–5.6, P = 0.034). Subgroup analysis showed that in participants with regular menstruation (OR 1.1, 95% CI: 1.0–1.3), WBC count was significantly different from irregular menstruation (OR 1.8, 95% CI: 1.2–2.8); P for interaction was 0.031. Conclusions: We found a reliable and non-linear relationship between WBC count and MTX treatment failure for EP.